The Elements of Drawing : John Ruskin's Teaching Collection - Ashmolean Museum (2007)
[Dt.:] Die Elements of Drawing Web Site bietet eine online Bilddatenbank und einen Katalog, der John Ruskin Teaching Collection. Diese Sammlung von Unterrichtsmaterialien des Künstlers, Sozialphilosophen und Kunsthistorikers John Ruskin (1819-1900) befindet sich im Ashmolean Museum und besteht aus Aquarellen und Zeichnungen Ruskins und seiner Mitarbeiter, aus dem 19. Jahrhundert stammende Photographien von Architektur und Kunst sowie aus Aquarellen, Zeichnungen und Drucken Alter Meister und zeitgenössischer Künstler wie William Turner, Edvard Burne-Jones und Albrecht Dürer. - [Engl.:] The Elements of Drawing is a searchable and browsable online catalogue, linked to digitised images, of John Ruskins Teaching Collection, held in the Ashmolean Museum. The Ruskin Teaching Collection was created to support the teaching of drawing in the Ruskin School of Drawing (established 1875). The collection, comprising the Standard, Educational, Reference, Rudimentary, and Supplementary Series, consisted of watercolours and drawings by Ruskin and his associates, nineteenth-century photographs of paintings and architecture, and a number of watercolours, drawings and prints by Old Master and modern artists notably Turner, Burne-Jones, and Dürer.